Determination of the instrument detection limit and dynamic range of flame AAS varian-55B for the metals Cd, Cu, Pb, and Zu - Erispe, Ma. Angelica Pioquinto (2008.)
The instrument detection limit (IDL) and dynamic range of Flame AAS Varian-55B in the chemistry laboratory, was determined for the metals cadmium, copper, lead, and zinc. The determination was done at different wavelengths at varying measurement times. The IDL is the minimum detection concentration for the instrument. It is one term which can describe instrument performance characteristics for an analyte element. The IDL determined at different measurement times was observed to vary, and no particular trend can be inferred from the results.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Instrument detection limit (IDL); Dynamic range of Flame AAS Varian-55B.